Early Experience of Oncological Reconstructive Surgery at Dharmais National Cancer Center - Rian Fabian Sofyan; Bayu Brahma; Iskandar Iskandar; Putri Naura (National Cancer Center - Dharmais Cancer Hospital, 2021)
Background: Oncological reconstructive surgery is a new paradigm in which it combines oncologic principles with reconstruction techniques. This study aims to present patients’ characteristics who had undergone oncological reconstructive surgery at the Department of Surgical Oncology, Dharmais National Cancer Center. Methods: This descriptive study identified patients’ characteristics who underwent oncological reconstructive surgery, their cancer types, and their therapies. All data were obtained from surgery registration and medical records from January 2019 to January 2020. Data were then presented in number and percentage.Results: A total of 174 patients had undergone oncological reconstructive surgery within one year. The mean age of all patients was 48.2 ± 16.7 years old. Most patients were female (72.1%), with breast cancer making up most cases (43.7%). Most of the participants also underwent mastectomy (42.1%), which was later followed by various reconstruction types. Sixty patients received free tissue transfer with microsurgery (34.4%), of which head and neck cancer constituted most cases. In addition, the most common donor site for the free flap was the Anterolateral Thigh (41.7%). Of all 174 patients, 75.2% presented with locally advanced cancer, and 17.8% had metastatic cancer. Within one year of follow-up, the survival rate was 87.4%, while local recurrence was 3%. Conclusions: The oncological reconstructive surgery approach plays a therapeutic and reconstructive role, and such might be the preferred method of choice for patients presenting with advanced-stage cancer